Analisis Keputusan Pedagang Nasi Kuning Dalam Menetapkan Waktu Berdagang Serta Dampaknya Terhadap Pendapatan - Agung Darmansyah Putra; Rosdiana Rosdiana (Jurnal Ecogen, 2023)
The objective of the study was to determine the effect of business location, age of workforce and working hours on the trading decisions of Nasi kuning traders wanting to sell in the morning and at night and whether there is a significant difference in income between the two types of Nasi kuning traders. The method used is associative and comparative methods. The collection techniques were observation, interviews and distribution of questionnaires which were distributed to 60 respondents where 30 respondents were selling in the morning and 30 respondents were selling at night. The analytical tools in this study are SEM-PLS and t-test analysis. The results showed that the age of the workforce did not have a significant effect on the trading decisions of Nasi kuning traders, business location and hours of work had a significant effect on the trading decisions of Nasi kuning traders, meanwhile there was a difference in income between Nasi kuning traders who sold in the morning and Nasi kuning traders who sold selling at night, where the net income of Nasi kuning traders who sell in the morning is greater than the Nasi kuning traders who sell at night.